HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHY FINGERPRINT PROFILE OF BAUHINIA TOMENTOSA LINN. LEAVES - R, Balabhaskar; K, Vijayalakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: Chromatographic fingerprint is an effective method for doing the fingerprinting of a plant species. In this study, high-performance thin-layer chromatography (HPTLC) analysis of Bauhinia tomentosa was done in n-hexane, chloroform, and ethanol extracts. Methods: The extract of leaves was developed using toluene:ethyl acetate:formic acid:glacial acetic acid (7:3:0.1:0.1) for n-hexane, toluene:ethyl acetate:formic acid (6:2:0.5) for chloroform, and chloroform:methanol:formic acid (8:1.5:0.2) for ethanol extract as mobile phase using standard procedures and scanned under ultraviolet at 254 nm, 366 nm, and 520 nm. Results: The HPTLC fingerprinting results showed several peaks with different Rf values. The HPTLC fingerprinting of n-hexane extract at 266 nm showed 15 peaks. The HPTLC fingerprinting of chloroform extract at 520 nm showed 22 peaks. The HPTLC fingerprinting of the ethanol extract at 366 nm showed 13 peaks. Conclusion: These fingerprinting results will be helpful in the identification and authentication of the species and also to identify new bioactive components in this medicinal plant.